Pengaruh APE Flashcard dan Permainan Lompat Lingkaran terhadap Kemampuan Budi Pekerti Anak Kelompok A di TK al-Abror - Heri Hidayat; Fadilla Ayuningtyas; Mutiara Syifa Azzahra; Siti Aneu Pratiwi Citra Lestari; Widadillah Nur Fatimah (YASIN, 2026)
The development of moral character in early childhood requires learning strategies that are concrete, enjoyable, and appropriate to children’s developmental characteristics. This study aims to analyze the effect of using educational play tools in the form of flashcards and jumping games on early childhood moral character abilities at TK Al Abror Arcamanik, Bandung City. This study used a quantitative approach with a quasi-experimental type and a one-group pretest-posttest design. The research subjects consisted of 10 Group A children aged 4–5 years selected through saturated sampling. Data were collected through structured observation using a validated and reliability-tested behavioral checklist observation sheet, and then analyzed using descriptive statistics and the Wilcoxon Signed Rank Test. The results showed an increase in the mean score from 11.1 in the pretest to 12.0 in the posttest, with an increase difference of 0.9 points. The Wilcoxon test obtained a significance value of 0.028 (p < 0.05), indicating a significant difference between scores before and after treatment. A total of 60% of children experienced an increase in scores, and all children who were initially in the Beginning to Develop (MB) category successfully improved to the Developing as Expected (BSH) or Developing Very Well (BSB) category, although the verbal reasoning indicator in the form of the ability to provide simple reasons did not show improvement. The conclusion of this study affirms that educational play tools in the form of flashcards and jumping games are effective as an innovative strategy for developing the affective and psychomotor aspects of early childhood moral character. The implications of this study indicate the need to strengthen reflective discussion sessions so that children’s cognitive-verbal abilities can develop more optimally.